2019
DOI: 10.1177/1533033818822329
|View full text |Cite
|
Sign up to set email alerts
|

Renal Cancer is Not Radioresistant: Slowly but Continuing Shrinkage of the Tumor After Stereotactic Body Radiation Therapy

Abstract: Purpose:To evaluate the safety and efficacy of stereotactic body radiation therapy for primary lesion of renal cell carcinoma with long-term and regular follow-up of tumor size and renal function.Methods:This prospective study included 13 patients treated with stereotactic body radiation therapy for primary lesion of stage I renal cell carcinoma between August 2007 and June 2016 in our institution. Diagnosis of renal cell carcinoma was made by 2 radiologists using computed tomography or magnetic resonance imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 37 publications
(60 reference statements)
1
23
0
Order By: Relevance
“…Overall, a dose-response relationship was established wherein every 10 Gy of physical dose to ipsilateral renal parenchyma predicts a GFR decrease of 25-39%. Regarding timing, an initial plateau phase followed by late-onset renal dysfunction !1 yr after SABR has been described previously [43,44] and is also noted in studies included here [37,38]. Taken together, these data indicate that careful treatment planning to minimize high-dose exposure of ipsilateral kidney parenchyma plus long-term follow-up ideally using functional imaging (ie, MAG3 or DMSA) will be important to capture late renal function decline in the targeted kidney.…”
Section: Renal Functionsupporting
confidence: 81%
See 1 more Smart Citation
“…Overall, a dose-response relationship was established wherein every 10 Gy of physical dose to ipsilateral renal parenchyma predicts a GFR decrease of 25-39%. Regarding timing, an initial plateau phase followed by late-onset renal dysfunction !1 yr after SABR has been described previously [43,44] and is also noted in studies included here [37,38]. Taken together, these data indicate that careful treatment planning to minimize high-dose exposure of ipsilateral kidney parenchyma plus long-term follow-up ideally using functional imaging (ie, MAG3 or DMSA) will be important to capture late renal function decline in the targeted kidney.…”
Section: Renal Functionsupporting
confidence: 81%
“…None of the 35 solitary kidney patients in this analysis required dialysis, suggesting that renal function may be adequately preserved even without compensation by the contralateral kidney. Of note, some included studies reported a late onset of renal dysfunction after SABR, with initial maintenance of baseline eGFR followed by a late decline [37,38]. Although direct comparison of renal function outcomes with surgical or TA management is difficult, our results are comparable with a previously reported large systematic review and meta-analysis comparing PN with TA, wherein median changes in eGFR (ranges) of -6.2 (-18 to +4.1) and -4.9 (-8.0 to +1.5) ml/min, respectively, were demonstrated [42].…”
Section: Renal Functionmentioning
confidence: 99%
“…Furthermore, the studies using a BED 10 range of 60-80 Gy with a median follow-up for ≥2 years reported a relatively low local control rates (range=85.7-89%) as shown in Table III (24,25). Conversely, local control rates in all the 3 studies and the in vivo 34: 2883-2889 (2020) present study using a BED 10 ≥90 Gy with a median followup of ≥2 years were higher than 90% (11,12,23). Taking the previous reports of SBRT and particle beam therapy together, BED 10 ≥90 Gy may be necessary and high-dose RT using advanced technology can accomplish good local tumor control.…”
Section: Discussionmentioning
confidence: 59%
“…However, an analysis of nine international multi-institutional studies of SBRT using a BED 10 range of 80-87.5 Gy reported a 4-year local control rate of 97.8% (20). Table III summarizes the clinical outcomes of previous studies evaluating RT for primary RCC (8,11,12,(22)(23)(24)(25). Those studies used a wide range of dose fractionation schedules and BED 10 values (range=38-125 Gy), but local tumor control was achieved in almost all patients irrespective of the BED 10 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, it was found that chemotherapy made KC patients decrease risk of CCD but increased risk of RCD, which was contrary to common sense owing to the bias existing in our study, one of the possible explanation was the patients received chemotherapy was with poor prognosis, but those who didn't received chemotherapy was with good prognosis that didn't need chemotherapy. Radiation therapy and chemotherapy were con rmed useful for KC treatment in many respects, such as reducing the risk of local recurrence 26 , delaying the metastasis of cancer 27 and so on 28 , but there were rare studies about the effect of radiation therapy and chemotherapy on CCD in KC patients. Further studies are expected to conduct in the clinic and laboratory to provide more information on the relationship between these two therapy methods and cardiovascular/cerebrovascular events in KC patients.…”
Section: Discussionmentioning
confidence: 99%